"I am Not a Failure": Embracing the Assets of Latinas in Continuation High Schools. Issue 5 (20th October 2022) - Hernandez, Edwin; Ortez, Johanna E.
ABSTRACT: This study centers the experiences of 9 Latinas enrolled in a continuation high school. This study attempts to understand how this continuation school engages with Latinas and attempts to improve their conditions and opportunities in this marginalized sector that is overrepresented with racially minoritized youth. Despite all the challenges they have encountered, their resiliency and agency was evident in their narratives as they remain hopeful and opmistic about their education and future. This study offers recommendations for continuation high schools on how to engage and support the educational aspirations of Latinas.